Development of Digital Literacy-Based Educational Games in Introduction to Coding for Early Childhood - Husni; Shofiyanti Nur Zuama; Amrullah; Andi Agusniatih (Al Hikmah Indonesian Journal of Early Childhood Islamic Education, 2026)
In recent years, research has shown that coding learning in early childhood can support computational thinking, problem solving and learning engagement, especially through game-based learning and unplugged coding approaches. The presence of digital technology in children's daily lives requires the assistance of parents and teachers so that its use continues to provide optimal benefits. A number of studies show that children need to be equipped with 21st century skills from an early age, such as critical thinking, problem-solving, creativity, collaboration, and the ability to use technology wisely. Initial observations in the B4 group of the Madani Integrated Model State Kindergarten, East Palu District showed a low interest in learning children, which was characterized by a lack of attention to teacher instruction and the lack of knowledge of basic coding concepts. This condition indicates the need for digital integration through interactive and fun learning media so that the learning process becomes more interesting and able to increase children's understanding of coding concepts. This research aims to develop and test the feasibility of digital literacy-based educational game media to introduce basic coding concepts. This research uses a Research and Development (R&D) approach with the ADDIE model. The subjects of the study were 15 children of the B4 group (10 boys and 5 girls). Data collection techniques include observation, interviews, documentation, and validation questionnaires. The results of expert validation showed that media experts (95.3%), and material experts (98.2%) were very qualified. The implementation resulted in cognitive improvement, in the aspects of recognizing colors, shapes, and grouping shapes, there were no children (0%) in the BSB and BB categories, 10 children (66.7%) in the BSH category, and 5 children (33.3%) in the MB category. In the aspect of recognizing colors, shapes, and grouping shapes, children showed high enthusiasm in using educational game media. The development of educational games based on digital literacy has proven to be feasible and effective in introducing coding, improving the cognitive abilities of B4 children, and overcoming the lack of focus on children's learning.